THE INFLUENCE OF BILINGUALISM ON COGNITIVE DEVELOPMENT IN EARLY CHILDHOOD - Tama, Sry; Damanik, Bernieke Anggita Ristia (Sindoro: Cendikia Pendidikan, 2025)
The phenomenon of bilingualism, which refers to the capacity to fluently use two languages, plays a significant role in shaping cognitive and social abilities, especially during early childhood—a period marked by rapid neurological and cognitive growth. This study explores how bilingualism influences critical cognitive domains such as executive functioning, problem-solving abilities, and social cognition in children aged 3–6 years. By comparing the performance of bilingual and monolingual children through structured cognitive and social tasks, the study reveals that bilingual children demonstrate superior abilities in cognitive flexibility, attentional regulation, and empathy. The findings emphasize the importance of fostering bilingual environments to support cognitive and social development during the formative years.